The Hydrophilicity of Samama Wood Surface Quality after Boron, Methyl Methacrylate Impregnation, and Heat Treatment - Cahyono, Tekat Dwi; Priadi, Trisna; Noviyanti, Eka; La Djumat, Juni; Kaliky, Fitriyanti (Jurnal Sylva Lestari, 2024)
Indicators of surface roughness and surface-free energy can represent the improvement in wood surface quality. In this study, those two indicators were used to determine the change in the samama (Anthocephalus macrophyllus) wood surface following two modification steps, namely impregnation and heat treatment. The first step was boron impregnation in two forms applied separately, i.e., boric acid and borax. The second step was impregnation of methyl methacrylate followed by heat treatment at 90°C and 180°C. Surface roughness was determined following the ISO 4287:1997 standard, and surface free energy was analyzed using the Rabel Method. The results showed that the radial surface of samama wood naturally had a lower roughness than the tangential surface. Impregnation with boric acid, borax, and methyl methacrylate increased the wood surface roughness. However, heat treatment at 180°C tended to smooth the rough surface. Total surface free energy was altered after borax and methyl methacrylate impregnation. However, heat treatment seemingly withdrew the alteration. The polar components and dispersion contributed to total surface free energy with different compositions. In this study, the change in surface roughness was not congruent with the change in total surface free energy. Keywords: boron, heat treatment, impregnation, samama, surface free energy